Social economics market behavior in a social environment - Becker, Gary S. (Gary Stanley) 1930- (Belknap Press of Harvard University Press, 2000)
This study of the choices people make draws together the conflicting beliefs of economists and other social scientists. The book includes the social environment with goods and services in its utility functions, providing analysis of how the individual and society interact.